University of Texas, Austin, Texas, United States of America - Thomson, Andrew; Swain, Madeleine (Geelong, Australia : World Wide Entertainment, 2007)
This documentary covers the events leading up to the 1966 University of Texas mass shooting and the nuclear disaster at Chernobyl in 1986.
Previously released on DVD.
Title from resource description page (viewed Sept. 1, 2011).
English.
Keywords: Whitman, Charles Joseph, -- 1941-1966.; University of Texas at Austin; Whitman, Charles Joseph, -- 1941-1966.; University of Texas at Austin; Chernobyl Nuclear Accident, Chornobylʹ, Ukraine, 1986.; Murder -- Texas -- Austin; Suicide -- Texas -- Austin; Chernobyl Nuclear Accident; Accident nucléaire de Tchernobyl, Tchernobyl, Ukraine, 1986.; Meurtre -- Texas -- Austin; Suicide -- Texas -- Austin; Murder; Suicide; Texas -- Austin; Ukraine -- Chornobylʹ; 1986; Documentary; Alexander Street Video; Documentary television programs; Nonfiction television programs; Documentary television programs; Nonfiction television programs; Documentaires télévisés.; Émissions télévisées autres que de fiction